Digital art - Paul, Christiane (London Thames & Hudson, 2015)
"Digital technology has revolutionized the way we produce and experience art today. Not only have traditional forms of art such as printing, painting, and photography and sculpture been transformed by digital techniques and media, but entirely new forms such as internet and software art, digital installation and virtual reality have emerged as recognized artistic practices." -- Provided by publisher
Introduction -- Digital technologies as a tool -- Digital technologies as a medium -- Themes in digital art
Includes bibliographical references (pages 264-265) and index.
Keywords: Computer art; Art and technology